SELF-EVALUATION OF GAMBELLA UNIVERSITY - Teresa, Tamrat Dina; Alemu, Jemberu; Kue, Luke; Berhe, Aregay; Taye, Endalkachew (International Journal of Research -GRANTHAALAYAH, 2018)
The major objective of this study was to investigate the quality of education, research and service delivery in Gambella University. To realize this objective, the summary write up was deployed the qualitative presentation of data and statistical records presentation of certain data of numerical values. Descriptive and explanatory research technique was also employed to narrate the audit outcomes. Systematic approaches using the computational techniques – SPSS and Excel 2010 has been used in the process of data analysis. This institutional quality audit report has provided a description and evaluation of the quality of Gambella University educational provision and of its mechanisms for assuring quality and relevance.